Why and how to create training sessions in the form of a game at a university? - Mariia I. Sharko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Based on the analysis of the scientific literature, the paper describes the signs of the game as a form of education at the level of higher education, its advantages and disadvantages, methodological recommendations for development. The results of the theoretical study are taken into account when preparing and conducting training sessions in a game form with university students. The generalization of work experience made it possible to determine the algorithm and methods for creating training sessions in a game form, techniques for providing the necessary pedagogical conditions to overcome the shortcomings of the game form. The algorithm includes: targeting based on the formed competence and type of occupation; Definition of activity content; development of a system of training assignments; identification of the features of the group affecting educational and gaming activities; determining a gaming base and a gaming task; selection of methods of influencing the emotional state of students; preparation of educational means. Popular games, plots of famous films are considered as the basis for creation. Two functions of game tasks are highlighted: to serve as a framework for solving the educational task (the quality of the educational task affects game achievements); provide an advantage when performing a training task. Pedagogical conditions for the organization of classes in the form of a game and techniques for their provision are determined: to prevent the fixation of attention exclusively on the game task, students are offered to predict the goal and upcoming activities on the basis of information about the formed competencies, summarizing the results after the completion of each game stage; to take into account the characteristics of the group the introduction of additional game conditions, modification of the game, organization of educational and gaming activities of each; to ensure compliance with ethical standards adaptation of well-known stories and forms, control by the teacher and the jury; to create a favorable psychological climate turning to popular stories and games, using provocative techniques; to provide an assessment system detailed instruction of jury members, use of various forms of assessment and presentation of work.